Defining a retailer's channel strategy applied to young consumers. Issue 11 (25th November 2014) - de Faultrier, Brigitte; de Faultrier, Brigitte; Boulay, Jacques; Feenstra, Florence; Muzellec, Laurent
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop an approach at defining a retail channel strategy applied to young consumers. Design/methodology/approach – The authors use a qualitative study that adopts the consumer perspective and employed an investiga-tive channel-scan approach based on two scenarios applied to 12 retailers selling childrenswear. The authors studied 139 flows between all the channels and explored the retailers' child orientation. Findings – The paper revealed that the channel configuration and integration of retailers showed a di-versity of approach leading us to distinguish eight different retail channel strategies. It also appears that there is limited evidence of a specific selling channels designed for children by retailers in selling products aimed at the child market. Research limitations/implications – This study contributes to the retail marking literature by showing evidence of child orienta-tion in channel management. Nevertheless, the results show the need for future research to understand the causes and effects of channel child orientation and the way it contributes to the retail channel strategy. Practical implications – The findings have practical implications for retailers by providing a framework to help them in their decision-making regarding retail channel strategy. It also sheds new light on the con-tribution from young consumers in retail channel strategy. Originality/value – The contribution of this paper is to explore the combined perspective of configuration and integration of the channel-to-market as part of the retail channel strategy. The paper also provides evidence of child orientation in retail channel strategy when retailers selling prod-ucts for children are concerned.